Transcriptomic and functional characterization of megakaryocytic-derived platelet-like particles: impaired aggregation and prominent anti-tumor effects - Kaitlin Garofano; Vera Mariani; Kameron Rashid; Sumanun Suwunnakorn; Alfateh Sidahmed; Anelia Horvath; Sanjay B. Maggirwar; Travis J. O’Brien; Minoli A. Perera; Michael Whalen; Norman H. Lee (Platelets)
Platelet-like particles (PLPs), derived from megakaryocytic cell lines MEG-01 and K-562, are widely used as a surrogate to study platelet formation and function. We demonstrate by RNA-Seq that PLPs are transcriptionally distinct from platelets. Expression of key genes in signaling pathways promoting platelet activation/aggregation, such as the PI3K/AKT, protein kinase A, phospholipase C, and α-adrenergic and GP6 receptor pathways, was missing or under-expressed in PLPs. Functionally, PLPs do not aggregate following epinephrine, collagen, or ADP stimulation. While PLPs aggregated in response to thrombin, they did not display enhanced expression of surface markers P-selectin and activated α2bβ3, in contrast to platelets. We have previously demonstrated that platelets physically couple to MDA-PCa-2b and RC77T/E prostate cancer (PCa) cells via specific ligand-receptor interactions, leading to platelet-stimulated cell invasiveness and apoptotic resistance, and reciprocal cell-induced platelet aggregation. In contrast, PLP interactions with PCa cells inhibited both cell invasion and apoptotic resistance while failing to promote PLP aggregation. Moreover, PLPs reduced platelet-PCa cell interactions and antagonized platelet-stimulated oncogenic effects in PCa cells. RNA-Seq analysis identified candidate ligand-transmembrane protein combinations involved in anti-tumorigenic signaling of PLPs to PCa cells. Antibody neutralization of the TIMP3-MMP15 and VEGFB-FGFR1 signaling axes reversed PLP-mediated anti-invasion and apoptotic sensitization, respectively. In summary, PLPs lack many transcriptomic, molecular and functional features of platelets and possess novel anti-tumorigenic properties. These findings indicate that PLPs may have a potential therapeutic role in targeting and disrupting the oncogenic signaling between platelets and cancer cells, offering a new avenue for anti-cancer strategies.